Pengaruh Kerjasama Garuda Indonesia dan Aliansi SkyTeam terhadap Industri Penerbangan di Indonesia - Toding, Valentine Boro (Universitas Bosowa, 2025)
This writing aims to determine the influence of Garuda Indonesia and SkyTeam Alliance Cooperation on the Indonesian Aviation Industry. From 2014 to the present, Garuda Indonesia and SkyTeam Alliance have collaborated to improve Garuda Indonesia’s reputation in the international arena, which is on par with other global airlines. This study uses the concept of International Cooperation to answer the formulation of the problem. The methods used in conducting this study are qualitative and descriptive. Data collection technique used is literature review from various relevant sources. The results show that through this collaboration, the increase in Garuda Indonesia’s reputation and increased connectivity impact the economic aspects of the Indonesian aviation industry. This influence is obtained through the increase in “Code Share” Cooperation with domestic and international routes, in this case, the increase in the number of passengers.